National cohort study comparing severe medium‐term urinary complications after robot‐assisted vs laparoscopic vs retropubic open radical prostatectomy. (15th November 2017) - Sujenthiran, Arunan; Nossiter, Julie; Parry, Matthew; Charman, Susan C.; Aggarwal, Ajay; Payne, Heather; Dasgupta, Prokar; Clarke, Noel W.; van der Meulen, Jan; Cathcart, Paul
Abstract : Objectives: To evaluate the occurrence of severe urinary complications within 2 years of surgery in men undergoing either robot‐assisted radical prostatectomy (RARP), laparoscopic radical prostatectomy (LRP) or retropubic open radical prostatectomy (ORP). Patients and Methods: We conducted a population‐based cohort study in men who underwent RARP ( n = 4 947), LRP ( n = 5 479) or ORP ( n = 6 873) between 2008 and 2012 in the English National Health Service (NHS) using national cancer registry records linked to Hospital Episodes Statistics, an administrative database of admissions to NHS hospitals. We identified the occurrence of any severe urinary or severe stricture‐related complication within 2 years of surgery using a validated tool. Multi‐level regression modelling was used to determine the association between the type of surgery and occurrence of complications, with adjustment for patient and surgical factors. Results: Men undergoing RARP were least likely to experience any urinary complication (10.5%) or a stricture‐related complication (3.3%) compared with those who had LRP (15.8% any or 5.7% stricture‐related) or ORP (19.1% any or 6.9% stricture‐related). The impact of the type of surgery on the occurrence of any urinary or stricture‐related complications remained statistically significant after adjustment for patient and surgical factors ( P < 0.01). Conclusion: Men who underwent RARP had the lowest risk of developing severe urinary complications within 2 years of surgery.